Therapeutic itineraries and testimonies of COVID-19 patients in Manaus, the epicenter of the pandemic in the Brazilian Amazon - Igor Castro Tavares; Denise Maria Guerreiro da Silva; Wagner Ferreira Monteiro; Kássia Janara Veras Lima; Darlisom Sousa Ferreira; Wuelton Marcelo Monteiro; Flávia Regina Souza Ramos (PLoS ONE, 2025)
Introduction Therapeutic itineraries (TIs) involve the process of choices and the evaluation of care/treatment experiences related to the family, popular and professional subsystems in the course of an illness. The understanding of TIs is fundamental not only in the human experiential sense, but also to subsidize transformations in health care systems. The objective of the study was to describe the therapeutic itineraries of patients with COVID-19 in the city of Manaus, which had the highest mortality rate and and was the epicenter of the disease in Brazil, while considering the severity of the health crisis in the scenario. Method A qualitative descriptive study that involved in-depth interviews of 29 patients who recovered from severe COVID-19 in Manaus, Brazil. Results The family and popular subsystems were integrated, and the professional subsystem was more prominent, given the conditions of initial ignorance about the disease and the serious repercussions of the epidemic. The TIs covered from the initial assessment of the health condition, available resources, information, access to health services to the worsening, hospitalization and perceived impacts of fear, scientific denial and unpreparedness and collapse of the system. Conclusions The reflection regarding objective and subjective behaviors of individuals in the health-disease process should last beyond the temporality of the crisis and mark the (re)construction of a resolutive health system that considers the real problems faced by users in the search for care.